Procesy inwolucyjne i ich uwarunkowania w układzie kostnym ludności średniowiecznej i współczesnej na przykładzie drugiej kości śródręcza - Rewekant, Artur (Polskie Towarzystwo Antropologiczne, 1996)
INVOLUTIONARY PROCESSES IN THE SKELETON OF MEDIAEVAL AND CONTEMPORARY POPULATIONS ON THE BASIS OF THE SECOND METACARPAL. The purpose of this paper is to present general trends in bone involution using second metacarpal in a mediaeval population and to compare the obtained results with data for contemporary groups. The findings may be valuable for the knowledge o f general and regional human skeletal ageing.
INVOLUTIONARY PROCESSES IN THE SKELETON OF MEDIAEVAL AND CONTEMPORARY POPULATIONS ON THE BASIS OF THE SECOND METACARPAL